Structure–activity relationship for the solid state emission of a new family of "push–pull" π-extended chromophores. (30th November 2016) - Nitti, Andrea; Villafiorita-Monteleone, Francesca; Pacini, Aurora; Botta, Chiara; Virgili, Tersilla; Forni, Alessandra; Cariati, Elena; Boiocchi, Massimo; Pasini, Dario
Abstract : We report the design, synthesis, molecular optical properties, and solid state emissive behaviour of a series of novel compounds, which, similar to the archetypal AIE luminogen tetraphenylethene, are formed of a central olefin stator and decorated with either three or four rotors. These rotors, being either electron-rich substituted benzenes, or electron-withdrawing functional groups (esters, ketones, cyano groups) confer a "push–pull" character to the overall molecular structure. Building on both new and already published contributions, a comprehensive picture of the properties and the potential of these compounds is provided.